Overview of the expression patterns and roles of Lipocalin 2 in the reproductive system - Krizanac, Marinela; Mass Sanchez, Paola Berenice; Weiskirchen, Ralf; Schröder, Sarah K. (Frontiers in Endocrinology, 2024)
The 25 kDa-sized protein Lipocalin 2 (LCN2) was originally isolated from human neutrophil granulocytes more than 30 years ago. LCN2 is an emerging player in innate immune defense, as it reduces bacterial growth due to its ability to sequester iron-containing bacterial siderophores. On the other hand, LCN2 also serves as a transporter for various hydrophobic substances due to its β-barrel shaped structure. Over the years, LCN2 has been detected in many other cell types including epithelial cells, astrocytes, and hepatocytes. Studies have clearly shown that aberrant expression of LCN2 is associated with a variety of disorders and malignancies, including several diseases of the reproductive system. Furthermore, LCN2 was proposed as a non-invasive prognostic and/or diagnostic biomarker in this context. Although several studies have shed light on the role of LCN2 in various disorders of the female and male reproductive systems, including tumorigenesis, a comprehensive understanding of the physiological function of LCN2 in the reproductive tract is still lacking. However, there is evidence that LCN2 is directly related to fertility, as global depletion of Lcn2 in mice has a negative effect on their pregnancy rate. Since LCN2 expression can be regulated by steroid hormones, it is not surprising that its expression fluctuates greatly during remodeling processes in the female reproductive tract, especially in the uterus. Well-founded details about the expression and regulation of LCN2 in a healthy reproductive state and also about possible changes during reproductive aging could contribute to a better understanding of LCN2 as a target in various diseases. Therefore, the present review summarizes current knowledge about LCN2 in the reproductive system, including studies in rodents and humans, and discusses changes in LCN2 expression during pathological events. The limited data suggest that LCN2 is expressed and regulated differently in healthy male and female reproductive organs.